Velocity and trajectory tracking control model for underactuated UUVs through coupling of direct CFD and PID control algorithm - Hou, Yuqing (2025)
Superior maneuverability is a crucial requirement for submarines and unmanned underwater vehicles (UUVs). However, there is a notable gap in closed-loop velocity and trajectory control methods for UUVs based on computational fluid dynamics (CFD) and control algorithms. To address this, an underactuated UUV motion control model combined with adaptive feedback regulation based on CFD is proposed, achieving a planned trajectory while maintaining a constant velocity for the first time. By coupling CFD field function program, overset mesh technology, sliding mesh technology, the line-of-sight (LOS) guidance algorithm, and the proportional-integral-derivative (PID) control algorithm, a numerical motion control for underactuated UUVs is developed to achieve simultaneous calculation of hydrodynamic characteristics and maneuverability, and the performance under various ocean current interference is verified. The results show that the maximum lateral deviation is less than 0.2 m, and the velocity control deviation is within 0.03 m/s for both motion cases. Additionally, the model demonstrates robust closed-loop control performance under current interference. This study provides a framework for the simultaneous calculation of hydrodynamic and closed-loop maneuvering performance, with significant implications for motion control and hydrodynamic optimization of underwater vehicles.